Implementation of Web-Based Augmented Reality on Hand-Held Display Using Marker Tracking Method: A Case Study of Mecca Florist - Jamila, Nur; Batupadang, Michael; Justan; Maun, Muh. Al (Cattleya Darmaya Fortuna, 2024)
Greeting Standing Flowers are used to convey congratulations or condolences. However, limitations in printed media and competition among artisans necessitate innovation. This study develops a Marker Tracking-based Augmented Reality (AR) application using ZapWorks Studio to display 2D animations, videos, typography, audio, sender contact information, Mecca Florist's social media, and a snapshot feature. The application development follows seven stages, including literature review, design, implementation, and testing. The test results indicate that the application meets the designed functional suitability criteria (x = 1). Usability testing yielded an average score of 90.87% (usefulness: 91.99%, ease of use: 87.8%, ease of learning: 90.85%, and satisfaction: 92.85%). In terms of performance efficiency, the application achieved an 86.67% success rate, with marker detection at angles between 45° and 135° and distances ranging from 200 cm to 400 cm. These results demonstrate that the AR application enhances the interactivity and attractiveness of Greeting Standing Flowers.